Challenges of Explicit and Implicit Communication A Relevance-Theoretic Approach - Jodlowiec, Maria (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2015)
Relevance Theory provides an original theoretical framework to capture the complex nature and intricacies of the processes underlying ostensive communication. The model has been in constant development for the last 30 years, and this study attempts to contribute to it by challenging free enrichment as an important explicature-generation procedure. The mechanisms underlying the recovery of explicitly and implicitly communicated meanings are explored in this book. They show that by approaching communication as a creative process, Relevance Theory offers a coherent explanation not only of communication in which what is conveyed is relatively straightforward and easy to identify, but also of cases in which what is communicated is partly precise and partly vague
Description based on publisher supplied metadata and other sources
Keywords: Psychologie; Communication models; Interpersonal communication; Semantics -- Psychological aspects; Sprache; Verbale Äußerung; Englisch; Implikatur; Pragmatik; Kommunikation; Relevanztheorie